AB0376 The efficacy of rituximab treatment for thrombotic thrombocytopenic purpura complicated with connective tissue disease. (23rd January 2014) - Susaki, K.; Dobashi, H.; Kameda, T.; Nakashima, S.; Shimada, H.; Ozaki, H.; Izumikawa, M.; Takeuchi, Y.; Yokoyama, T.; Matsunaga, T.
Abstract : Background: Rituximab has been used widely and established the key role for B-cell lymphoma treatment. Rituximab is a chimeric monoclonal antibody bound to the CD20 antigen present on the surface of normal and malignant B lymphocytes, also expected to induce apoptosis of the CD-20-positive B cells, and acts through B cells depletion that play an important role on humoral immunity in connective tissue diseases (CTD). Recently, it has been reported that Rituximab was effective for patients with several autoimmune diseases. Currently, Rituximab is not only approved for B-cell lymphoma, but also for Rheumatoid arthritis or ANCA-associated vasculitis in United States or Europe. It also comes to known the efficacy of B-cell depletion therapy for autoimmune associated hematological disorders complicated with CTD. B-cell depletion is supposed to current attractive therapy for the autoimmune diseases especially in hematologic disorders complicated with CTD that contribute to various self-antigens in its etiology. Autoimmune thrombocytopenic purpura (AITP), autoimmune hemolytic anemia (AIHA) and thrombotic thrombocytopenic purpura (TTP) are common hematological manifestations associated with CTD. Above all, TTP with CTD sometimes causes significant morbidity and mortality, and are refractory to conventional immunosuppressive therapy and/or plasma exchange (PE). We now focused on TTP with CTD and investigated short and long-term efficacy of Rituximab treatment in our facility. Objectives: We investigate the short- and long-term efficacy of Rituximab for TTP with CTD. Methods: We retrospectively studied TTP with CTD that was administered Rituximab in our facility between 2009-2012. Six patients of TTP with CTD (2 patients with SLE, 3 with Sjögren syndrome, 1 with Dermatomyositis) were received Rituximab. All patients were resisted conventional immunosuppressive therapy (corticosteroid, cyclophosphamide, cyclosporin etc.) and/or PE. Every case was injected Rituximab (375 mg/m 2 ) at 0 and 14 weeks. Results: Six patients were responded after initial infusion of Rituximab and improved thrombocytopenia. Five patients who had psychological disorder also improved their symptoms from several weeks to 2 months after Rituximab injection. But one had no response to the treatment. Additionally, these patients have sustained in remission after the treatment of Rituximab for at least 6 months. Adverse event such as infusion reaction or progressive multifocal leukoencephalopathy (PML) were not seen in our cases. Conclusions: CTD with TTP is sometimes refractory to conventional therapy and occurred severe outcome. Rituximab could be an effective tool for TTP with CTD treatment in Japanese patients. The efficacy could be expressed immediately and sustained for long time. This agent could be first line effective agent for TTP with CTD. But it has been reported of several issues that developed PML on cases that treated with Rituximab for autoimmune diseases. We need to pay attention for long-term adverse events. Disclosure of Interest: None Declared